2016
DOI: 10.1002/ente.201500458
|View full text |Cite
|
Sign up to set email alerts
|

Process Comparison for Biomass Combustion: In Situ Gasification‐Chemical Looping Combustion (iG‐CLC) versus Chemical Looping with Oxygen Uncoupling (CLOU)

Abstract: Biomass is an interesting renewable fuel to be used in chemical looping combustion (CLC). If the CO2 generated during biomass combustion is captured, the negative‐CO2 emission concept is possible. This work evaluates the differences between biomass combustion under two CLC configurations developed for solid fuels: in situ gasification‐chemical looping combustion (iG‐CLC) and chemical looping with oxygen uncoupling (CLOU). The combustion efficiency, tar emission, and carbon capture efficiency obtained at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…found when biomass was burned [29]. Traditionally, Cu-or Mn-monometallic oxides supported on an inert material have been proposed for their use in CLOU [30].…”
Section: Similar Differences In Performance Between Both Types Of Chementioning
confidence: 99%
“…found when biomass was burned [29]. Traditionally, Cu-or Mn-monometallic oxides supported on an inert material have been proposed for their use in CLOU [30].…”
Section: Similar Differences In Performance Between Both Types Of Chementioning
confidence: 99%
“…Furthermore,t he difference between iG-CLC and CLOU operation using biomass as fuel was also investigated in terms of combustion efficiency and carbon capturee fficiency. [12] Thes tudies mentioned here have concluded that, in general, al ow oxygen carrier circulation rate is required for CLOU as compared to CLC to accomplish biomass combustion. Most of the experimental studies have provided ap ositive mandatet od evelop and scale-upt he CLC and CLOU process to an industrial level using biomass as fuel.…”
Section: Introductionmentioning
confidence: 84%
“…[2] CLOU does not involve the gasificationo f the fuel char;h ence the rate of combustion in the fuel reactor is high compared to CLC. [12] It shows that compared to CLC,t he residence time of oxygen carrier particles in the fuel reactor is also less.A saresult, the fluidizatione nergy cost is lower in CLOU compared to CLC.I th ad been reported that the fluidization agent does not have any influence on the decomposition of oxygen carrier particlesi nt he fuel reactor. [18] Hencei nt he present simulation, N 2 is useda s af luidization agent as per experimental worko fG ue tal.…”
Section: Clou Of Biomassmentioning
confidence: 99%
“…Some research works have been concluded that direct CLC of solid fuels lead to the formation of unconverted char in the fuel reactor and burning of fuel in the air reactor [30]. Thus, to reduce the above mentioned difficulties a new technology named In-situ Gasification Chemical Looping combustion (IGCLC) was introduced where the gas released from the gasification of solid fuels will be used as a fuel in CLC process [31]. Adánez-Rubio I., et al demonstrated CLOU concept for the first time with biomass as fuel in a continuous CLC unit using milled pine wood chips with 60% of CuO contained oxygen carrier prepared by spray drying method where full conversion of biomass has been taken place [32].…”
Section: Clc Of Gas Obtained From Biomassmentioning
confidence: 99%